A Comparative Analysis of Large Deformation Behavior of Thin Flat and Corrugated Steel Plates Under Static and Blast Loading - Erkmen, Bülent; Sarı, Ali; Öztürk, Sezer (Techno-Press, 2025)
This paper investigates the large deformation behavior of thin flat and corrugated (crimp) steel plates used in prefabricated blast-resistant modular structures through finite element simulations. The study evaluates plate responses under static monotonic, cyclic static, and dynamic blast loads using pressure-impulse (P-I) curves. Closed-form models based on yield line theory are developed to predict deflection-pressure curves for both flat and corrugated plates, showing strong agreement with finite element analysis. The results indicate that the pressure-deformation behavior of flat plates changes significantly upon yielding. Under cyclic loading, their stiffness decreases substantially until membrane action mitigates the effects during unloading, which also results in a notable reduction in hysteretic energy dissipation capacity. In contrast, the cyclic analysis of corrugated plates reveals decreased load-carrying capacity due to buckling from their profile, yielding, and plastic deformations. However, these plates exhibit substantial energy dissipation and maintain consistent initial stiffness throughout hysteretic loops, with minimal deviation. The findings highlight the significant influence of aspect ratio on plate behavior. Flat plates show a highly sensitive pressure-displacement relationship based on their aspect ratio, while corrugated plates exhibit minimal sensitivity in both static and dynamic conditions. Corrugated plates display consistent one-way bending behavior, largely independent of their aspect ratio. Dynamic blast analysis reveals that corrugated plates perform better in impulse-sensitive regions across all response levels, while flat plates excel in pressure-sensitive regions, particularly at medium and high levels.
Keywords: Blast; Corrugated plate; Large plate deflection; Membrane action; Modular steel building